2015
DOI: 10.1111/sum.12165
|View full text |Cite
|
Sign up to set email alerts
|

Crop rotation and seasonal effects on fatty acid profiles of neutral and phospholipids extracted from no‐till agricultural soils

Abstract: Analysis of phospholipids (PLFA) and neutral lipids fatty acids (NLFA) was used to characterize no‐till productive agricultural soils associated with different crop rotation levels, replicated across a 400 km transect in the Argentinean pampas, during two sampling seasons, summer and winter. High rotation (HR) management consisted in maize–wheat–soybean intense rotation including cover crops. Low rotation (LR) management trend to soybean monocultures. Soils from nearby natural environments (NEs) were used as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 45 publications
(71 reference statements)
1
23
0
Order By: Relevance
“…Most fatty acids obtained in this study had been found previously when the same set of samples was analysed by the PLFA/NLFA method (Ferrari et al ., ). Nevertheless, there were several fatty acids in the WSFA profile that were not found in the previous analysis with the PLFA/NLFA method.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Most fatty acids obtained in this study had been found previously when the same set of samples was analysed by the PLFA/NLFA method (Ferrari et al ., ). Nevertheless, there were several fatty acids in the WSFA profile that were not found in the previous analysis with the PLFA/NLFA method.…”
Section: Resultsmentioning
confidence: 97%
“…Several fatty acids were exclusively extracted with the WSFA approach, not being found in the PLFA/NLFA method applied to the same soil sample set (Ferrari et al ., ). Fernandez et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations